Meningkatkan Aktivitas dan Hasil Belajar Siswa Muatan Matematika menggunakan Model BEST di Kelas IV SDN Antasan Besar 1 Banjarmasin - Dina Afriani; Herti Prastitasari (CV. ITTC INDONESIA, 2023)
The problem in this study is the low activity and learning outcomes. This is caused by ineffective learning and low understanding of mathematical concepts. One of the efforts to overcome this problem is to conduct learning using the BEST model. The purpose of this study was to analyze students' activities and learning outcomes. This research uses qualitative and quantitative data with the type of Classroom Action Research (PTK) conducted with four meetings. The subjects of this study were 14 fourth grade students of SDN Antasan Besar 1 Banjarmasin in the second semester of the 2022/2023 school year. The results of this study indicate that students' activities and learning outcomes have increased until the 4th meeting reached 100%. Based on the results of this study, it can be concluded that the use of the BEST model can be implemented so as to increase student learning activities and outcomes. The findings of this study can also be used as a guide in developing learning models to improve students' mathematics learning activities and outcomes.